Efficacy, tolerability, patient usability, and satisfaction with a 2 mL pre-filled syringe containing secukinumab 300 mg in patients with moderate to severe plaque psoriasis: results from the phase 3 randomized, double-blind, placebo-controlled ALLURE study. (3rd April 2022) - Sigurgeirsson, Bardur; Schäkel, Knut; Hong, Chih-Ho; Effendy, Isaak; Placek, Waldemar; Rich, Phoebe; Keefe, Deborah; Bruin, Gerard; Charef, Pascal; Fu, Rong; Hampele, Isabelle; Patekar, Manmath
Abstract: Background: Evidence shows good tolerability in patients for subcutaneous injection volumes up to 3 mL. Objectives: We investigated efficacy, pharmacokinetics, and tolerability of secukinumab 300 mg/2 mL pre-filled syringe (PFS) in patients with moderate to severe plaque psoriasis. Methods: ALLURE was a 52-week, multicenter, randomized (1:1:1), double-blind, placebo-controlled, parallel-group study. Co-primary endpoints were secukinumab Psoriasis Area Severity Index (PASI) 75 and Investigator's Global Assessment modified 2011 0/1 (IGA mod 2011 0 or 1) responses at week 12 versus placebo. Other endpoints included the Self-Injection Assessment Questionnaire (SIAQ), and the ability to follow the instructions for use (IFU). Results: Overall, 214 patients were randomized. The secukinumab 300 mg/2 mL PFS showed superiority over placebo for both PASI 75 (88.9% versus 1.7%; p <.0001) and IGA mod 2011 0 or 1 (76.4% versus 1.4%; p <.0001) responses at week 12. All secondary efficacy endpoints were met. The SIAQ scores were similar across groups and improved similarly over 12 weeks. All patients completed critical steps in the IFU at week 1. Conclusions: The secukinumab 300 mg/2 mL PFS groups showed superiority versus placebo, and it was a safe, effective, and convenient option for patients with psoriasis. NCT02748863.